A Study on Prevalence of Reproductive Tract Infections Amongst Women Attending in an Urban Clinic - Khan, Kabir Ahmed; Islam, Sk Md. Jaynul; Akhter, Shirin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Introduction: One element of reproductive health that directly concerns human well being is reproductive tract infections (RTI). The magnitude of the problem of RTIs is a growing public health concern in developing countries like Bangladesh. Aim: A study was carried out in the out patient department of a busy urban clinic with an attempt to study the Reproductive Tract Infections (RTIs). Materials and Methods: A descriptive type of cross sectional study was carried out in the Gynaecology OPD of an urban clinic at Dhaka, the capital of Bangladesh during the period from July 2007 to December 2007. The study population includes the women of reproductive age group (15-49 years). Among 1061 reported women 176 respondents were selected for the study with a systematic purposive sampling technique. Data were collected from prescription sheets of the concerned gynecologist, laboratory investigation reports and questionnaires used for interview. Results: Mean age of the respondents was 30.56+6.1. Among 176, 174 (98.86%) were married. Depending on clinical symptoms 32 (18.19%) were diagnosed as RTI, after clinical examinations 39 (22.16%) and while after laboratory investigations 42 (23.9%) were diagnosed as RTI. Among 39 provisionally diagnosed RTI cases 13 (33.33%) were diagnosed as PID, 10 (25.64%) as mixed infection and 05 (12.82%) as vulvovaginitis clinically. Among 42 confirmed RTI cases 16 (38.09%) were confirmed as bacterial vaginosis, 04 (9.52%) as trichomoniasis, 07 (16.66%) as candidiasis, 06 (14.28%) as mucopurulent cervicitis while 01 (2.38%) was diagnosed as syphilis. Among 28 abortion cases 10 (35.71%) developed RTI while among 38 MR cases 18 (46.36%) developed RTI. Among 34 IUD users 22 (64.7%) developed RTI while for other contraceptive method users only 19 (15.8%) developed RTI. Conclusion: Although the study was in a limited scale and the findings of it will not only serve as a guideline for taking preventive measures, but can be used as a basis for future research and planning. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19415